The Leadership Lab for Women: Advancing and Retaining Women in STEM through Professional Development - Van Oosten, Ellen B.; Buse, Kathleen; Bilimoria, Diana (Frontiers in Psychology, 2017)
Innovative professional development approaches are needed to address the ongoing lack of women leaders in science, technology, engineering, and math (STEM) careers. Developed from the research on women who persist in engineering and computing professions and essential elements of women’s leadership development, the Leadership Lab for Women in STEM Program was launched in 2014. The Leadership Lab was created as a research-based leadership development program, offering 360-degree feedback, coaching, and practical strategies aimed at increasing the advancement and retention of women in the STEM professions. The goal is to provide women with knowledge, tools and a supportive learning environment to help them navigate, achieve, flourish, and catalyze organizational change in male-dominated and technology-driven organizations. This article describes the importance of creating unique development experiences for women in STEM fields, the genesis of the Leadership Lab, the design and content of the program, and the outcomes for the participants.